Gender-Stratified Factors Associated with Stigma Toward HIV/AIDS among Rural Communities in Sarawak, Malaysia - Aren, Sinedeh Lemin; Md Mizanur, Rahman; Andrew, Kiyu (FACULTY OF MEDICINE AND HEALTH SCIENCES, UPM, 2022)
Introduction: Many factors hinder the effective responses to the HIV/AIDS epidemic. Stigma is one of the major barriers to effective responses to the HIV/AIDS epidemic. It is often considered the main reason for the low response to access proper services for prevention, treatment, and care for HIV/AIDS. In this context, we assessed the perceived level of stigmatisation towards people with HIV/AIDS among rural communities in Sarawak and determined its associated factors. Methods: This cross-sectional community-based study was conducted among the adult population aged 18 years and above among rural communities in Sarawak, Malaysia. A gender-stratified multistage cluster sampling technique was adopted to select the respondents. A total of 900 respondents were successfully interviewed using interviewer-guided questionnaires. Stepwise multiple linear regression with forward and backward selection method was used to determine the HIV/AIDS-related stigma. A p-value of ≤.05 was considered statistically significant. Results: Analysis revealed that females are more stigmatised than males (p<.05). Multivariate analysis showed that those who did not know someone had HIV and Chinese ethnicity were potential predictors in both male and female groups. Having no gainful job, and discussion of HIV/AIDS, household income less than MYR 500, history of HIV testing, knowledge on HIV transmission and exposure to HIV/AIDS information were factors that influenced HIV/AIDS-related stigma among female respondents. On the other hand, age group 30 to 39, Bidayuh, Chinese ethnicity, and not knowing someone had HIV and media exposure on HIV were factors that influenced HIV/AIDS-related stigma among male respondents. Conclusion: HIV/AIDS-related stigma towards HIV/AIDS existed in rural communities. Enhanced health promotion related to HIV/AIDS activities in rural communities are needed to curb stigmatisation toward people with HIV/AIDS.